2018
DOI: 10.3906/vet-1709-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine hydrochloride on growth promotion in guinea pigs (Cavia porcellus)

Abstract: Ractopamine hydrochloride (R) is commonly used in the livestock industry, mainly in pork and beef, to improve feed efficiency and productivity. In the present study, the use of R at different doses (20 ppm, 30 ppm, or 40 ppm) on growth performance and carcass characteristics of guinea pigs (male and female) was explored with a view to achieving greater use of this species for human consumption. Thirty-two clinically healthy guinea pigs at an average age of 5 weeks were used. The daily gain, feed over gain rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Concerning KR in particular, its decline during the post-weaning period could be because this trait is correlated with feed conversion efficiency and energy requirement for maintenance, both of which are also known to decline with increasing age and body mass (Roshanfekr 2014;Harper 1998;Thompson et al, 2010;Nie et al, 2015;Jeichitra et al, 2014). Numerous studies have also reported variation in AGR, RGR, AMR and/or KR between growth phases and/or sexes in various domestic animals (Ghafouri-Kesbi and Tari 2015; Supakorn and Pralomkrn 2012;Zuñiga-Galindo et al, 2018;Khadda et al, 2018;Chakraborty et al, 2020;Bansal et al, 2021;Tesema et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning KR in particular, its decline during the post-weaning period could be because this trait is correlated with feed conversion efficiency and energy requirement for maintenance, both of which are also known to decline with increasing age and body mass (Roshanfekr 2014;Harper 1998;Thompson et al, 2010;Nie et al, 2015;Jeichitra et al, 2014). Numerous studies have also reported variation in AGR, RGR, AMR and/or KR between growth phases and/or sexes in various domestic animals (Ghafouri-Kesbi and Tari 2015; Supakorn and Pralomkrn 2012;Zuñiga-Galindo et al, 2018;Khadda et al, 2018;Chakraborty et al, 2020;Bansal et al, 2021;Tesema et al, 2021).…”
Section: Discussionmentioning
confidence: 99%